Neoadjuvant and Adjuvant Therapy for Renal Cell Carcinoma - Naomi B. Haas; Jeffrey Shevach; Ian D. Davis; Tim Eisen; Marine Gross-Gupil; Anil Kapoor; Viraj A. Master; Christopher W. Ryan; Manuela Schimdinger (Société Internationale d’Urologie Journal, 2022)
Patients undergoing definitive surgery or ablative techniques for nonmetastatic kidney cancer have varying degrees of risk of recurrent disease post procedure. The ultimate goal of “adjuvant therapy” is to reduce the incidence of recurrent disease, and to cure more patients. We summarize the current state of perioperative therapy for kidney cancer and explore future directions to develop optimal adjuvant strategies. We define risk and risk of recurrence post-definitive therapy, describe the controversies surrounding the trial landscape of adjuvant vascular endothelial growth factor receptor tyrosine kinase inhibitors and immune checkpoint inhibitors. We review data on neoadjuvant therapy before advanced kidney cancer resection. Radiologic, ethnic, economic, and geographic considerations with respect to adjuvant therapy are highlighted, as well as adjuvant therapy issues especially pertinent to patients, future directions in adjuvant trial design specifically targeted to biomarkers and patient selection, and sequencing of treatment after adjuvant therapy in those patients with recurrence.